Bigger, Brighter, Bluer-Better? Current Light-Emitting Devices – Adverse Sleep Properties and Preventative Strategies - Gringras, Paul; Middleton, Benita; Skene, Debra J.; Revell, Victoria L. (Frontiers in Public Health, 2015)
Objective In an effort to enhance the efficiency, brightness and contrast of light-emitting (LE) devices during the day, displays often generate substantial short-wavelength (blue-enriched) light emissions that can adversely affect sleep. We set out to verify the extent of such short-wavelength emissions, produced by a tablet (iPad Air), e-reader (Kindle Paperwhite 1st generation) and smartphone (iPhone 5s) and to determine the impact of strategies designed to reduce these light emissions. Setting University of Surrey dedicated chronobiology facility. Methods Firstly, the spectral power of all the light-emitting (LE) devices was assessed when displaying identical text. Secondly, we compared the text output with that of ‘Angry Birds’-a popular top 100 ‘App Store’ game. Finally we measured the impact of two strategies that attempt to reduce the output of short-wavelength light emissions. The first strategy employed an inexpensive commercially available pair of orange-tinted ‘blue-blocking’ glasses. The second tested an app designed to be ‘sleep-aware’ whose designers deliberately attempted to reduce blue-enriched light emissions. Results All the LE devices shared very similar enhanced blue-light peaks when displaying text. This included the output from the backlit Kindle Paperwhite device. The spectra when comparing text to the Angry Birds game were also very similar, although the